NU (NAHDLATUL ULAMA) DAN WACANA RADIKALISME AGAMA (Analisis Terhadap Majalah Risalah Tahun 2011-2012) - Arsam, Arsam (Fakultas Dakwah IAIN Purwokerto, 2013)
Risalah is a monthly magazine, in other words, the magazine is published once a month. Themagazine is published by the Central Board of Nahdlatul Ulama. The entire of NU figures in thehigh ranks of management that exist in this magazine are the contributors as well as. NU throughRisalah is excited to elevate the discourse of religious radicalism, criticized the movementcarried out by means of violence and provide solutions to overcome the problem of discourse ofreligious radicalism. Of the NU discourse constructed through Risalah, and contributors who areall derived from Boards of NU, it leads to Ahlussunnah waljamaah that transcendental humanistideology emphasizes attitude of moderate, Tasamuh, tawasut, tolerant and amar ma’ruf nahimunkar in religious, social, national and state life.